Elevated Levels of Galectin-9 but Not Osteopontin in HIV and Tuberculosis Infections Indicate Their Roles in Detecting MTB Infection in HIV Infected Individuals - Shete, Ashwini; Bichare, Shubhangi; Pujari, Vishwanath; Virkar, Rashmi; Thakar, Madhuri; Ghate, Manisha; Patil, Sandip; Vyakarnam, Annapurna; Gangakhedkar, Raman; Bai, Gaowa; Niki, Toshiro; Hattori, Toshio (Frontiers in Microbiology, 2020)
Galectin-9 (Gal-9) and Osteopontin (OPN) play immunomodulatory roles in tuberculosis and HIV infections. Evaluation of their levels as well as their interplay with different pro-inflammatory cytokines is critical to understand their role in immunopathogenesis of HIV/tuberculosis coinfection considering the complexity of the disease. Plasma levels of these proteins were measured by ELISAs in HIV negative individuals with pulmonary (n=21), extrapulmonary (n=33), latent tuberculosis (n=22) and in HIV infected patients with pulmonary (n=14), latent tuberculosis (n=17) and without tuberculosis (n=41). Levels of pro-inflammatory cytokines were estimated by luminex assay. Receiver operated characteristic curve analysis was performed to evaluate discriminatory roles of these proteins. Spearman correlation analysis was performed with the markers of HIV and tuberculosis disease progression to evaluate their immunopathogenic roles. Gal-9 and OPN levels were higher in HIV uninfected patients with active tuberculosis than with latent tuberculosis. Gal-9 but not OPN levels were higher in HIV infected patients with active tuberculosis than with latent tuberculosis. Area under curve for Galectin-9 was >0.9 in HIV/tuberculosis coinfection and extrapulmonary tuberculosis. OPN and IL-6 levels were higher in patients with severe chest X-ray grade indicating its association with severity of the disease and positively correlated with each other. Stronger positive and negative correlations of Gal-9 levels respectively with viral loads and CD4 cell counts in HIV infected patients were observed than OPN levels indicating their association with HIV disease progression. Thus, significantly elevated Gal-9 levels were reported for the first time in HIV/tuberculosis coinfection and extrapulmonary tuberculosis in our study than single infections with HIV and tuberculosis. The study indicated a need for further evaluation of monitoring role of Gal-9 for detection of developing tuberculosis in HIV infected individuals. The findings also indicated differential roles of Gal-9 and OPN in pathogenesis of tuberculosis and HIV infections.